Ore Mineralogy and its Relevance for the Selection of Concentration Methods in the Processing of Brazilian Iron Ores - S C. Amarante; C C. Souza; A C. Arauj (The Australasian Institute of Mining and Metallurgy, 2002)
All major companies now producing iron ore in Brazil currently employ or are planning to employ some sort of concentration method to upgrade their fine sized products (sinter feed fines and pellet feed fines). The criteria for the selection of the most suitable concentration method for each application include a series of parameters; the most important among them being related to ore mineralogy. This paper reviews the concentration operations currently employed in Brazil and shows how ore mineralogy plays a fundamental role in the selection of a given method. Examples involving gravity concentration (jigs and spirals), magnetic separation (Rare Earth wet drums, ferrous wheel, and Jones type magnetic separators) and flotation (especially column flotation) are discussed. Fundamentally important for the selection of a concentration method is the mineralogy of iron-bearing minerals and gangue minerals presented to the feed to the concentration unit operation. For instance, the presence of liberated quartz as the major gangue mineral for a pellet feed size stream generally indicates that flotation will be the best selection for the concentration of that stream. However, even if magnetite is present only in the form of crystal relicts within hematite grains, it may lead to the selection of either magnetic separation alone or a combination of magnetic separation and flotation for concentrating such material. Presence of gibbsite and/or kaolinite as the major phase containing alumina will also affect the selection of the concentration method in all cases. Again for the case of pellet feed size streams, kaolinite does not interfere with flotation whereas gibbsite tends to contaminate flotation concentrate (pellet feed fines) as it is depressed together with iron oxides and hydroxides during the reverse cationic flotation process.